Implementasi Karakter Peduli Lingkungan di Prodi PGSD Muara Bulian - Muhammad Sholeh (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study continues the research on the effect of the concept of environmental education on environmental care knowledge of elementary school teacher education students studied by Aisyah Fitria. In the results of the study, the concept of environmental education affects the knowledge of environmental care for elementary school teacher education students. The results of the study indicate that the concept of environmental education affects the knowledge of environmental care for elementary school teacher education students. It can be said from previous research that there is an effect of the concept of environmental education on knowledge about the environment for elementary school teacher education students in Jambi University experimental class from pretest to posttest. Based on observations on elementary school teacher education students, researchers found that there were still many students who threw garbage in classrooms, campus yards, did not care about plants on campus, besides that students often did not tidy up chairs and tables after using the study room. Lack of awareness of students to maintain, feel that they have a place for the environment and learning facilities. The results of this observation are also supported by documents on environmental conditions on campus